2017
DOI: 10.1590/s1980-6574201700si0008
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal insulin signaling and neuroprotection mediated by physical exercise in Alzheimer´s Disease

Abstract: -Epidemiological studies indicate continuous increases in the prevalence of Alzheimer's Disease (AD) in the next few decades. The key feature of this disease is hippocampal neurodegeneration. This structure has an important role in learning and memory. Intense research efforts have sought to elucidate neuroprotective mechanisms responsible for hippocampal integrity. Insulin signaling seems to be a very promising pathway for the prevention and treatment of AD. This hormone has been described as a powerful activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Mechanisms may vary according to phenotype. Insulin's signaling pathway drives cellular responses (e.g., gene transcription), and protein translation and transport (43, 44). McNay et al (25) showed that intrahippocampal delivery of insulin, and not IGF-1, enhanced spatial working memory via PI3K pathways, and that blockage of endogenous hippocampal insulin impaired cognitive performance.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms may vary according to phenotype. Insulin's signaling pathway drives cellular responses (e.g., gene transcription), and protein translation and transport (43, 44). McNay et al (25) showed that intrahippocampal delivery of insulin, and not IGF-1, enhanced spatial working memory via PI3K pathways, and that blockage of endogenous hippocampal insulin impaired cognitive performance.…”
Section: Discussionmentioning
confidence: 99%
“…Among these regions, the hippocampus plays an important role in storing new memories [ 77 ]. During normal physiological conditions, insulin and growth factors like BDNF, insulin like growth factors 1 and 2 (IGF-1 and 2) and VEGF transmit intracellular signals in the hippocampal neurons for their integrity and to keep hippocampus functional [ 78 ]. However, when the functionality of these growth factors is inhibited, the possibility of AD becomes high [ 78 ].…”
Section: The Role Of Exercise In Neurological Diseases and Involvementioning
confidence: 99%
“…However, forced exercise(running daily for 20 min for two weeks)reversed this effect in 20 month-old rats [ 79 ]. PE has been shown to exert anti-inflammatory effects and enhances insulin signaling in the hippocampal neurons [ 78 ]. PE also elicits an insulin sensitizing effect in the peripheral nervous system [ 80 ] and hence the possibility of it to bring about the same effect in the central nervous system and play a neuroprotective role is quite possible [ 81 ].…”
Section: The Role Of Exercise In Neurological Diseases and Involvementioning
confidence: 99%
“…However, recent evidence has shown that it also affects nerve cells and plays an important role in hippocampal neurogenesis and neuroprotection [113]. As BDNF or IGF-1, exercise-induced VEGF may have a role in ameliorating the pathological process of AD [114]. Moreover, VEGF, because of its active role in neurogenesis, may mediate antidepressant therapies [115].…”
Section: Vascular Endothelial Growth Factor (Vegf)mentioning
confidence: 99%